2007
DOI: 10.1128/jcm.02071-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Staphylococcus saprophyticus Isolated from Women with Uncomplicated Community-Acquired Urinary Tract Infection

Abstract: Staphylococcus saprophyticus is a common cause of urinary tract infections (UTIs) in women. Little is known about the molecular epidemiology of S. saprophyticus UTIs. In the current study, we compared 76 isolates of S. saprophyticus prospectively isolated from women with uncomplicated UTI participating in a randomized placebo-controlled treatment trial performed in northern Sweden from 1995 to 1997 with 50 strains obtained in 2006 from five different locations in northern Europe with pulsed-field gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…On the other hand, the results of PFGE profiling and Southern hybridization for the other five isolates revealed different patterns, suggesting that multiple mecA-positive S. saprophyticus strains might circulate in Japanese communities. Similar to our observation, Widerstrom et al also reported that multiple clones of S. saprophyticus were associated with lower UTIs in women (24).…”
Section: Resultssupporting
confidence: 81%
“…On the other hand, the results of PFGE profiling and Southern hybridization for the other five isolates revealed different patterns, suggesting that multiple mecA-positive S. saprophyticus strains might circulate in Japanese communities. Similar to our observation, Widerstrom et al also reported that multiple clones of S. saprophyticus were associated with lower UTIs in women (24).…”
Section: Resultssupporting
confidence: 81%
“…In northern climates, there is marked seasonal variation in the incidence of S. saprophyticus UTI (Rupp et al, 1992; Hovelius and Mårdh, 1984; Ringertz and Torssander, 1986; Hedman et al, 1993; Widerström et al, 2007), whereas there is no evidence of seasonality in Mediterranean climates (Schneider and Riley, 1996). S. saprophyticus can be identified in environmental samples, with a strong seasonal peak that occurs just before peak rates of S. saprophyticus UTI in northern climates (Hedman et al, 1993; Soge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…S. saprophyticus can be identified in environmental samples, with a strong seasonal peak that occurs just before peak rates of S. saprophyticus UTI in northern climates (Hedman et al, 1993; Soge et al, 2009). Molecular epidemiological surveys also suggest S. saprophyticus is primarily acquired from an environmental reservoir, rather than as a result of person-to-person transmission (Widerström et al, 2007; Widerström et al, 2012). These observations suggest that the bacteria cycle between host-associated and environmental stages, with seasonal climatic effects on their abundance in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Few English-language studies have typed collections of S. saprophyticus by pulsed field gel electrophoresis (PFGE) and none of these studies were supported by epidemiological data. In a large study with isolates from women with uncomplicated UTI, the PFGE genotypes of 76 isolates collected in Northern Sweden from 1995-1997 were compared with 50 isolates obtained from five different locations in Northern Europe in 2006 (Widerström et al 2007). Ten PFGE genotypes, including those with up to three band differences and similarities (Dice coefficient) of 85-100%, were identified.…”
mentioning
confidence: 99%